THE CONSTITUTIONAL COURT'S DECISION ON CHILD OUT OF WEDLOCK IS BASED ON JUSTICE - Didik Suhariyanto (Jurnal Pembaharuan Hukum, 2022)
The aim of this research is to find out and analyze the justice-based review of out-of-wedlock children as a result of the decision of the constitutional court, the implications of the Constitutional Court's decision have provided a new legal breakthrough for the realization of perfecting the legal position of illegitimate children whose regulation. The approach method in this study used a normative juridical approach, the results obtained that The Constitutional Court's decision Number 46/PUU-VIII/2010 has fulfilled the principle of justice, namely the principle of child protection and is an acknowledgment of children's human rights. For children out of wedlock, the Constitutional Court's decision has fulfilled their desire for legal certainty and justice, as well as responding to the subjective sense of injustice that they have felt so far. The decision of the Constitutional Court Number: 46/PUU-VIII/2010 has provided an opportunity for children out of wedlock to be able to obtain law enforcement on the existence of their position as a child due to the marital relationship between their mother and biological father.